Sejarah Penyebaran Islam Di Sumedang Melalui Pendekatan Budaya - Gina Luthfiatin; Aam Abdillah (Priangan: Journal of Islamic Sundanese Culture, 2022)
Religion is an element of culture, so religion and culture are inseparable. Cultural acculturation is one of the methods of spreading Islam that is most quickly accepted by the community, because it can accept foreign culture and process it into its own culture without causing the loss of the cultural elements of the group itself. Like the entry of Islam to Sumedang, it brought changes in socio-cultural life with the Islamic values contained therein, but this did not eliminate the previous culture but still existed in the midst of society. The method in this research uses historical methods, namely heuristics, criticism, interpretation and historiography.